2015
DOI: 10.12693/aphyspola.128.b-201
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Shielding Properties of Concrete and Ferro-Boron

Abstract: The problem of shielding against high-energy neutrons has always attracted a great deal of attention. Neutron shielding requires slowing down energetic neutrons and absorbing with a shield material. Concrete is one of the best known materials for neutron shielding and ferro-boron is described as an alternative shielding material in this study. FLUKA Monte Carlo simulation code was used for the application of shielding calculation. When the simulation results are compared, it is clear that ferro-boron is more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…* corresponding author; e-mail: nbozkurt@beu.edu.tr Sarıyer et al [3] investigated neutron shielding properties of concrete and suggested the usability of ferro-boron in concrete in a form of particle alloy. Özavcı and Çe-tin [4] emphasized that with the growing population, the amount of waste also increases.…”
Section: Introductionmentioning
confidence: 99%
“…* corresponding author; e-mail: nbozkurt@beu.edu.tr Sarıyer et al [3] investigated neutron shielding properties of concrete and suggested the usability of ferro-boron in concrete in a form of particle alloy. Özavcı and Çe-tin [4] emphasized that with the growing population, the amount of waste also increases.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the simulated results, it shows that the exposure room shielding containing Ferro boron concrete manage to reduce the radiation dose rate by 1150%. It is known that Ferro boron is a great material for radiation shielding especially for neutron radiation due to boron contents [16,20]. With the new exposure room shielding, the NURI facility at RTP can ensure the safety of all the users and the surrounding environment at all times.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a new design of exposure room shielding for the Neutron Radiography Imaging (NURI) facility at RTP is presented. This new shielding contains Ferro boron as coarse aggregates to enhance its shielding capability [20]. Initial study of using concrete containing Ferro boron had been done before, which lead to determine the ideal thickness and Ferro boron contents for the concrete [16].…”
Section: Figure 1 Top View Of Puspati Triga Mark II Nuclear Research ...mentioning
confidence: 99%
“…The shielding materials could reflect or slow down neutrons, causing them to disintegrate into alpha and beta particles. [ 5–8 ] Despite the fact that lead is the most extensively utilized neutron shielding material, researchers have been working to replace it with bio‐friendly alternatives due to its toxicity and production limitations. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%